A Comparative Discourse on Istidlāl Hadīṡ for the Recitation of Basmalah in Prayer: Perspectives of Nahdlatul Ulama and Muhammadiyah: Kajian Komparatif mengenai Istidlāl Hadīṡ Bacaan Basmalah dalam Shalat: Perspektif Nahdlatul Ulama dan Muhammadiyah - Khoirul Mubin; Toha Harun Al Rasyid; Unzilatun Nikmah; Rodli al Anshori (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
The discourse surrounding the recitation of Basmalah in Al-Fatihah during prayer has consistently been a contentious issue within society, particularly between members of Nahdlatul Ulama (NU) and Muhammadiyah. This divergence arises from differences in perspectives and variations in the interpretation of istidlāl (legal reasoning) derived from hadith used by both groups. This study examines the methods and approaches employed by NU and Muhammadiyah in understanding, interpreting, and formulating legal rulings based on hadith. The research focuses on two primary questions: First, what methods are implemented by NU and Muhammadiyah in istidlāl hadith? Second, what narrations serve as their foundational basis for legal rulings? These questions are explored through a descriptive-analytical method grounded in literature review. The findings reveal that; first, NU and Muhammadiyah each have dedicated institutions tasked with understanding Islamic legal sources and issuing fatwas—namely, the Lembaga Bahtsul Masail for NU and the Majelis Tarjih for Muhammadiyah; second, Nahdlatul Ulama employs the qauly, ilhaqy, and manhajy methods in interpreting Islamic legal sources, whereas Muhammadiyah utilizes the bayani, ta'lili, and istishlahi methods; and third, Regarding the recitation of Basmalah in prayer, NU considers it obligatory and recommends its recitation aloud (jahr), based on istidlāl qauli referring to Imam Shafi'i's opinion in Al-Umm. In contrast, Muhammadiyah allows for Basmalah to be recited either silently (sirr) or aloud (jahr), using the bayani method, which draws on hadith narrated by Imam Malik in Al-Muwatta’, offering a more flexible interpretation of the recitation of Basmalah.